Case Control Study of Post-endoscopic Variceal Ligation Bleeding Ulcers in Severe Liver Disease: Outcomes and Management - Jamwal, Kapil D. (J Clin Transl Hepatol, 2019)
Background and Aims: The management of post-endoscopic variceal ligation (EVL) bleeding ulcers (PEBUs) is currently based on local expertise and patients liver disease status. The present retrospective study investigated associations between the endoscopic morphology of PEBUs and patient outcomes. Methods: Patients underwent EVL (primary or secondary), from January 2015 to January 2018, in two tertiary care hospitals in India (ILBS New Delhi and Dharamshila Narayana New Delhi). Mortality rates were determined at post-EVL day five and week six. PEBUs were typified based on Jamwal & Sarin classification system as follows: A, ulcer with active spurting; B, ulcer with ooze; C, ulcer base with visible vessel or clot; and D, clean or pigmented base. Results: Of 3854 EVL procedures, 141 (3.6%) patients developed PEBU, and 46/141 (32.6%) suffered mortality. Among the former, the PEBU types A, B, C, and D accounted for 17.7, 26.2, 36.3, and 19.8%, respectively. Of those who died, 39.1, 30.4, 21.7, and 8.8% had PEBU types A, B, C, and D. Treatments included transjugular intrahepatic portosystemic shunts (TIPS), esophageal self-expandable metal stent (SEMS), glue and sclerosant injection, Sengstaken-Blakemore tube placement and liver transplant. On univariate analysis, no correlation with hepatic venous pressure gradient, TIPS placement, size of varices, or number of bands was found. The Model for End-Stage Liver Disease (MELD)-sodium score correlated positively with outcome. After adjusting for MELD-sodium score, mortality was best predicted by type-A ulcer (p = 0.024; OR 8.95, CI 1.34–59.72). Conclusions: PEBU occurred in 3.6% of a large EVL cohort. Stratifying patients based on PEBU type can help predict outcomes, independent of the MELD-sodium score. Classifying PEBUs by endoscopic morphology may inform treatment strategies, and warrants further validation.